Type 2 diabetes mellitus in elderly patients treated with endocrinologists in clinical practice - Elena V. Biryukova (Endocrinology Research Centre, 2019)
A large-scale epidemic of type 2 diabetes mellitus (T2DM) is observed with advanced ageing worldwide. The prevalence of T2DM significantly increases with age. Therefore, this review aimed to summarise the data on T2DM in advanced and older aged patients. The primary geriatric syndromes, which should be considered for the management of older patients (cognitive impairment, sarcopenia, orthostatic hypotension, falls, urinary incontinence, senile asthenia, etc.), are presented. The causes of the high risk for hypoglycaemia in elderly patients are analysed. Improving the treatment for T2DM is a priority of modern medicine. Using antihyperglycaemic therapy is especially difficult in this population due to the high risk of hypoglycaemia and the multi-organ pathology leading to polypharmacy. Therefore, special attention is paid to treatment recommendations. Hypoglycaemic drugs used in elderly patients should be low risk of hypoglycaemia, without nephro- and hepatic toxicity, safe for cardiovascular organs, easy to administer. Furthermore, advantages and limitations of using various groups of hypoglycaemic drugs in elderly patients are discussed. DPP-4 inhibitors are also considered in detail. Modern data on mechanisms of hypoglycaemic action of DPP-4 inhibitors are presented. Possibilities of using sitagliptin in elderly patients were also considered. Finally, evidence-based studies demonstrating the obvious advantages of sitagliptin for the treatment of T2DM in the elderly and advanced aged population are discussed.